Integrated Islamic-Western Education as Predictor of Muslim Youths’ Moral and Academic Development - Adam Olasunkanmi Kewulere; Isiaq Oluwatosin Yahya; Basit Alabi Saliu (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study explores the impact of integrated Islamic and Western education on youth development outcomes, specifically moral and academic growth, among Muslim youths in Lagos, Nigeria. Employing a cross-sectional design, data were collected from 84 Muslim youths in the Ajegunle-Apapa community through convenience sampling. The